2018
DOI: 10.1002/cbic.201800446
|View full text |Cite
|
Sign up to set email alerts
|

A Unified View of Assessing the Pro‐oxidant versus Antioxidant Nature of Amyloid Beta Conformers

Abstract: Transition-metal-catalyzed oxidative stress is a widespread concern in the pathogenesis of Alzheimer's disease. However, the exact role of amyloid beta oligomers towards oxidative stress is widely debated. Assessing the oxidative nature of the oligomers in vitro is complicated by the different experimental conditions under which they are prepared. We have investigated Cu -catalyzed reactive oxygen species (ROS) generation by using oligomers prepared in phosphate-buffered saline (Aβ ) and in cell culture medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
1
11
0
Order By: Relevance
“…by coumarin‐3‐carboxylic acid (3‐CCA) assay. Consistent with our previous results, [50] we find that the degree of ROS generation is dependent on the aggregation state of Aβ 42 . As seen from the Asc oxidation presented in Figure 2A–C, the Aβ O−PBS (Figure 2B, black) consumed Asc the fastest compared to the monomers (Aβ M ) (Figure 2A, black), fibrils (Aβ F−PBS ) (Figure 2C, black), and free Cu 2+ in solution (Figure 2A, orange).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…by coumarin‐3‐carboxylic acid (3‐CCA) assay. Consistent with our previous results, [50] we find that the degree of ROS generation is dependent on the aggregation state of Aβ 42 . As seen from the Asc oxidation presented in Figure 2A–C, the Aβ O−PBS (Figure 2B, black) consumed Asc the fastest compared to the monomers (Aβ M ) (Figure 2A, black), fibrils (Aβ F−PBS ) (Figure 2C, black), and free Cu 2+ in solution (Figure 2A, orange).…”
Section: Resultssupporting
confidence: 93%
“…The chelator should also bind both redox states of Cu, redox silence Cu, and kinetically remove Cu 2+ faster from the Cu−Aβ complex [49] . In this regard, several natural products, [50–52] peptide‐based inhibitors, [26,28] and synthetic molecules [38,40,53,54] have been investigated to mitigate the effect of Aβ‐induced AD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Aβ peptides are incapable of inducing cell death at a <5 μM concentration [ 21 , 31 ] ( Figure 2 ), they can significantly induce inflammatory responses from ARPE cells, leading to degeneration and accelerated senescence [ 32 , 33 ]. Surprisingly, Aβ peptides were not found to induce oxidative stress in NGC0211 cells, which may be attributed to the antioxidant properties of soluble Aβ [ 34 , 35 ]. Nonetheless, we showed that Aβ peptides and inflammatory molecules, such as IL-1β and TNFα, can severely impair NGC0211 cell proliferation when exposed directly ( Figure 3 , Figure S5B ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, ROS facilitate the formation of neurofibrillary tangles by promoting the misfolding and cross-linking of proteins [ 23 , 47 , 48 ]. Some studies reported the potential role of Aβ monomers as antioxidants, depending on the metal ion concentration in vitro [ 49 , 50 ]. In contrast, other studies showed that oligomeric Aβ, the dominant form in patients with AD, promotes ROS production in cooperation with metal ions in vitro and in vivo [ 51 , 52 , 53 , 54 ].…”
Section: Dysregulation Of Redox Homeostasis In Neurodegenerative Diseasesmentioning
confidence: 99%